Javanese Culture In Elementary School Class II Fine Arts Education For The Preservation Of Local Wisdom - Aprilia Dita Maliana; Vanda Rezania (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
The integration of local Javanese culture into Fine Arts education for second-grade elementary students is a strategic response to globalization challenges, emphasizing the need to strengthen cultural identity from an early age. This research explores the significance of embedding local culture in Fine Arts education, highlighting its accessibility and relevance to young learners. A qualitative methodology is adopted, with data collected through interviews, observations, documentation, and literature reviews. Instruments include observation sheets, interview templates, and documentation forms. The study is conducted at a State Elementary School recognized for effectively incorporating local cultural preservation within its curriculum. Findings indicate that integrating Javanese culture in Fine Arts education enables students to connect directly with their environment, fostering a deeper appreciation for local wisdom and ensuring its sustainability. This initiative underscores the role of education in nurturing cultural identity, preparing students to navigate global influences while preserving their heritage.